Utilização da proteína HSP70 na otimização de método diagnóstico imuno-histoquímico para detecção de formas amastigotas de protozoários do gênero Leishmania - Pedro Paulo de Abreu Teles (2018)
Leishmaniasis corresponds to a group of infectoparasitary diseases caused by protozoa of the Leishmania species. Developed by Tafuri, et. al (2004), the alternative technique of Immunohistochemistry (IHQ) which uses hyperimmune serum to Leishmania infantum in naturally infected dogs as primary antibody showed to be effective for the detection of amastigote forms of Visceral Leishmaniasis (VL) and American Cutaneous Leishmaniasis (ACL). Three of the most common species in the state of Minas Gerais, L. infantum, L.(V.)amazonensis and L.(V.) braziliensis had the proteomic characterization of their antigens to determine their immunogenic reactivities to the dog hyperimmune serum. In this study we describe the standardization of a new IHQ protocol using rabbit serum sensitized by the antigen HSP70 as primary antibody aiming at the comparison and enhancement of the technique in order to improve the diagnosis in dogs infected by Leishmania spp. Duplicate histological sections were analyzed according to the two applied techniques of IHQ. A 100% correlation was obtained in the classification of reative amastigote forms, both when using hyperimmune serum from naturally infected dogs or rabbit serum sensitized by the antigen HSP70. For that semiquantitative analysis of the reaction a score was established based on the number of fields with immunolabeled amastigotes, ranging from 1 (0 -15 fields), 2 (15-30 fields) to 3 (> 30 fields) according to the infection level and the results were: 1) twenty (68,9%) histological sections; 2) one (3,5%) histological sections and 3) eight (27,6%) histological sections. Quantitative study was carried out by optical microscopy and morphometrical analysis. Twenty five images were randomly chosen and used to count immunolabeled amastigotes. The images were analyzed by software, viewed on a computer video screen and sent to a computer-assisted image analysis system KS300 (Carl Zeiss®, Germany). The program Prism 5.0 was used for the analyses. There was no statistical difference between IHQ tests (P<0,05). Thereby the results demonstrated that it was possible to obtain the labeling of amastigote forms through this IHQ test made from the rabbit serum sensitized by the antigen HSP70. Improvements in technique for background reduction have yet to be performed. The use of the primary rabbit antibody production could allow for the creation of a better IHQ diagnosis process.